Determinants of Visit Decisions in Cultural Tourism: A Quantitative Approach - Islamey, Disa; Eddyono, Fauziah (Advances in Tourism Studies, 2024)
Understanding the factors that influence visitor decisions is crucial for enhancing the competitiveness of cultural heritage tourism. This study examines the effects of attraction attributes, amenities, accessibility, and motivation on visitors’ decisions to visit heritage destinations. Employing a quantitative approach, data were collected through a structured questionnaire from 163 respondents using simple random sampling. Multiple linear regression analysis was conducted using SPSS to test the relationships among the variables, complemented by perception mapping to identify priority areas for improvement. The results reveal that attraction attributes, amenities, and accessibility have significant positive effects on visit decisions, while motivation does not show a statistically significant impact. Additionally, the perception map indicates that several key indicators require management attention, particularly in enhancing accessibility and certain service facilities. The findings suggest that destination managers should focus on improving infrastructure and maintaining core attractions to sustain visitor interest. This study contributes to the understanding of visitor behavior in heritage tourism and offers practical implications for destination development and strategic planning.